Evolutionary history and divergence times of Tettigoniidae (Orthoptera) inferred from mitochondrial phylogenomics - Zhao, Tianyou; Lin, Zhenbin; Yang, Hailin; Song, Fan; Xia, Zhenyuan; Huang, Weidong (Frontiers in Genetics, 2025)
BackgroundAdvances in high-throughput sequencing technology have led to a rapid increase in the number of sequenced mitochondrial genomes (mitogenomes), ensuring the emergence of mitochondrial phylogenomics, as a powerful tool for understanding the evolutionary history of various animal groups.Methods In this study, we utilized high-throughput sequencing technology to assemble and annotate the mitogenomes of Letana rubescens (Stål) and Isopsera denticulata Ebner. We described the characteristics of the mitochondrial genes of these two species. Utilizing 13 PCGs and 2 rRNA genes, we reconstructed the phylogenetic relationships of Tettigoniidae by combining published data with our newly generated data. We used likelihood mapping, signal-to-noise ratio (SNR), and saturation analysis across different datasets to ensure the robustness of our inferred topologies.Results and conclusionSelective pressure analysis on the 13 protein-coding genes (PCGs) and 2 ribosomal RNA (rRNA) genes revealed that only ND1 and COX1 contained positively selected sites, while negative selection dominated across all genes, indicating that mitochondrial genes primarily function to maintain genetic integrity. Additionally, we assessed the evolutionary rates of the 13 PCGs and two rRNA genes across five major subfamilies using mean pairwise identity analysis. Phylogenetic results of our study provide more precise insights into the relationships within Tettigoniidae, spanning subfamilies, tribes, genera, and species. We further estimated the divergence times of Tettigoniidae using four fossil calibration nodes in MCMCTree, dating the origin of katydids to the early Paleogene period (approximately 60.86 Mya), and identifying the divergence nodes for five major subfamilies.